Effects of speed on temporal patterns in freestyle cross-country skiing - Nilsson, J.; Tveit, P.; Eikrehagen, O. (2002)
The purpose of this study was to investigate temporal patterns in the movement cycle and its adaptation to speed in freestyle cross-country skiing. Eight skilled male cross-country skiers volunteered as subjects in the study. A flat snow strip approximately 60 m long and 5 m wide was prepared for freestyle cross-country skiing. The subjects performed four freestyle techniques; gear 2 "paddle dance", gear 3 "double dance", gear 4 "single dance" and gear 5 "combiskate". The four techniques were each performed at four different speed levels in the order; slow, medium, fast (perceived competition speed) and maximum speed. The subjects were recorded with a digital video camera at 50 frames per second. The calculation of average speed, determination of movement phases and analyses of the temporal patterns were performed by means of a video analysis system. Cycle duration, cycle rate, cycle length, phase duration, and relative and absolute cycle duration at different speeds were analyzed. The cycle rate in all tested freestyle cross-country skiing techniques was found to increase significantly (P<0.01) with speed from slow to maximum speed (i. e. a significant decrease in cycle duration). The increase in cycle rate was approximately doubled over the whole velocity range. The decrease in cycle duration was accompanied with a significant decrease in the absolute phase durations of all investigated skiing techniques (P<0.01). A striking finding was also the constant relative phase duration with speed which indicates a simplified neural control of the speed adaptation. A minor change in cycle length and a significant increase in cycle rate with speed showed that freestyle cross-country skiing to a large extent is dependent on an increase in cycle rate for speed adaptation.